Evaluating the Effectiveness of First-Time Methadone Maintenance Therapy Across Northern, Rural, and Urban Regions of Ontario, Canada - Eibl, Joseph K. (J Addict Med, 2015)
Our objective was to determine the impact that a patient's geographic status has on the efficacy of first-time methadone maintenance therapy (MMT) retention. METHODS: We conducted an observational cohort study using administrative health care databases for patients who commenced methadone therapy between 2003 and 2012. Patients were stratified on the basis of their location of residence into 1 of 4 groups—Southern Urban, Southern Rural, Northern Urban, or Northern Rural. The primary outcome was continuous retention in treatment, defined as 1 year of uninterrupted therapy on the basis of prescription refill data. Mortality was measured as a secondary outcome. RESULTS: We identified 17,211 patients initiating first-time MMT during this 10-year period. Nearly half of patients initiating therapy in northern regions completed 1 year of treatment (48.9%; N = 258 and 47.0%; N = 761 in Northern Rural and Urban regions, respectively), whereas lower rates of 40.6% (N = 410) and 39.3% (N = 5,518) occurred in Southern Rural and Urban regions, respectively. Patients residing in Northern Rural and Northern Urban regions were 31% (adjusted odds ratio = 1.31; 95% confidence interval [CI], 1.09%–1.58%] and 14% (adjusted odds ratio = 1.14; 95% CI, 1.02%–1.27%] more likely to be retained in treatment compared with those residing in Southern Urban regions. There was no significant difference in treatment retention between those residing in Southern Rural and Southern Urban regions. A mortality rate of 3% was observed within 1 year of patients initiating treatment, with patients in the Southern Rural region having the highest rate (4.85%). CONCLUSIONS: Our study identified regional differences in retention rates and mortality of first-time MMT. These findings may relate to geographic isolation and limited methadone program availability experienced in northern regions. We interpret the data to suggest that patients who have reduced access to treatment experience higher retention rates when they are able to access therapy.